2008
DOI: 10.4049/jimmunol.181.3.2196
|View full text |Cite
|
Sign up to set email alerts
|

The PDE4 Inhibitor Rolipram Prevents NF-κB Binding Activity and Proinflammatory Cytokine Release in Human Chorionic Cells

Abstract: Spontaneous preterm delivery is linked to intrauterine inflammation. Fetal membranes are involved in the inflammatory process as an important source of mediators, and the chorion leave produces high levels of the proinflammatory cytokine TNF-α when stimulated by LPS. The transcription factor NF-κB is the main regulator of this inflammatory process and controls the production of cytokines by the chorion leave. Phosphodiesterase 4 inhibitors are recognized for their anti-inflammatory and myorelaxant effects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
1
25
1
Order By: Relevance
“…Administration of LPS (30mg/kg) into adult C57BL/6J mice increased circulating concentrations of the pro-inflammatory cytokines (TNFα, IL12β) and promoted lethality within 1–2 days (Figures 1A,B and S1A). Co-administration of the phospho-diesterase 4 (PDE4) inhibitor Rolipram (5mg/kg) blocked effects of LPS on cytokine release and survival (Figures 1 and S1) (Herve et al, 2008). Moreover, exposure of cultured bone marrow macrophages (BMMs) to prostaglandin E2 (PGE2), a paracrine hormone that stimulates cAMP production (Okonogi et al, 1991), reduced pro-inflammatory cytokine mRNA amounts and secretion from cultured cells exposed to LPS (Figures 1C,D and S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Administration of LPS (30mg/kg) into adult C57BL/6J mice increased circulating concentrations of the pro-inflammatory cytokines (TNFα, IL12β) and promoted lethality within 1–2 days (Figures 1A,B and S1A). Co-administration of the phospho-diesterase 4 (PDE4) inhibitor Rolipram (5mg/kg) blocked effects of LPS on cytokine release and survival (Figures 1 and S1) (Herve et al, 2008). Moreover, exposure of cultured bone marrow macrophages (BMMs) to prostaglandin E2 (PGE2), a paracrine hormone that stimulates cAMP production (Okonogi et al, 1991), reduced pro-inflammatory cytokine mRNA amounts and secretion from cultured cells exposed to LPS (Figures 1C,D and S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in other systems have shown that PDE4 inhibitors can inhibit NF‐ κ B p65 activation and NF‐ κ B‐driven inflammatory mediator release (Herve et al. 2008; Kwak et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cAMP-specific PDE4 regulates LPS-TLR4 induced inflammatory cytokine expression in mouse models of liver fibrosis, a condition commonly attributed to alcohol abuse [70]. Finally, PDE4 inhibitors have been shown to reduce NF-κB binding, leading to decreased inflammatory cytokine production in macrophages [71]. A promis-future science group Review Warden, Erickson, Robinson, Harris & Mayfield ing preliminary study by Avila et al [72] showed that alcohol-induced activation of astrocytes and microglia in mouse brain was attenuated in PDE4b knockout mice and by pharmacological inhibition using a PDE4 inhibitor (rolipram, 5 mg/kg).…”
Section: Tlr-specific Drugs Alter Alcohol Consumptionmentioning
confidence: 99%